2019
DOI: 10.1021/acsomega.9b02639
|View full text |Cite
|
Sign up to set email alerts
|

Toughening Biosourced Poly(lactic acid) and Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) Blends by a Renewable Poly(epichlorohydrin-co-ethylene oxide) Elastomer

Abstract: A series of sustainable polymer blends from renewable poly(lactic acid) (PLA), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3,4HB), and poly(epichlorohydrin-co-ethylene oxide) (ECO) elastomer were fabricated via a melt blending method to gain balanced physical performance. The interplay of the composition, mutual miscibility, and viscosity ratio of the pristine PLA, P3,4HB, and ECO elastomer resulted in diverse phase structures of the ternary blends. An excellent flexibility at an elongation of 270% was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In the present work, the film of the neat PLA prepared by the solution-casting method exhibits better ductility compared to the results of samples obtained by melt-processing in previous reports. 35,36 This outcome suggests that the thermal stability of PLA is very important for the melt-processing of PLA. Blending 20 wt % ECO into PLA increased the elongation at break of PLA to approximately 110%, and this increase is consistent with previous reports.…”
Section: Phase Morphologymentioning
confidence: 92%
See 1 more Smart Citation
“…In the present work, the film of the neat PLA prepared by the solution-casting method exhibits better ductility compared to the results of samples obtained by melt-processing in previous reports. 35,36 This outcome suggests that the thermal stability of PLA is very important for the melt-processing of PLA. Blending 20 wt % ECO into PLA increased the elongation at break of PLA to approximately 110%, and this increase is consistent with previous reports.…”
Section: Phase Morphologymentioning
confidence: 92%
“…ECO was selected because it is a potential toughening agent for PLA-based materials. 35,36 As a typical stiff A-b-C compatibilizer, the influence of the composition and chain structure of the PLA-b-PMMA block copolymer on the miscibility, morphology, crystallization behavior, and mechanical properties of the PLA-based blends was thoroughly investigated. The native compatibilization and toughening mechanisms of the PLA/ECO/PLLA-b-PMMA blends were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…23 It was also frequently reported that PHAs in PLA/PHAs blends served as nucleating agents to promote the crystallization of PLA, such as PHB, 24 PHBV, 25 and P34HB. 26 Besides, the PHB phase also served as a spherulite growth-accelerating agent to accelerate the crystallization of PLA. 27 Nevertheless, the understanding remains superficial or even contradictory on the role of PHAs playing on the nucleating and plasticizing.…”
mentioning
confidence: 99%
“…Recently, we also studied renewable copolymerized epichlorohydrinethylene oxide rubber as toughening agent for renewable PLA and P 34 HB blends through the melt processing method. 19 However, several main challenges still greatly limited effectiveness of the multiphase blending strategy for the bio-polyesters blends. One problem is the poor miscibility of PLA or PHAs with other biobased polyesters, which was pursued to be resolved by adding copolymer compatibilizer or reactive compatibilization.…”
Section: Introductionmentioning
confidence: 99%
“…Favis et al 18 have systemically studied a series of biobased polyesters multiphase blends and made great contribution for understanding the phase structure. Recently, we also studied renewable copolymerized epichlorohydrin‐ethylene oxide rubber as toughening agent for renewable PLA and P 34 HB blends through the melt processing method 19 . However, several main challenges still greatly limited effectiveness of the multiphase blending strategy for the bio‐polyesters blends.…”
Section: Introductionmentioning
confidence: 99%